The effect of milk-feeding method and hay provision on the development of feeding behavior and non-nutritive oral behavior of dairy calves - Horvath, K.C.; Miller-Cushon, E.K. (Journal of dairy science, 2017)
We investigated the interactive effects of common feeding management factors on the development of feeding and non-nutritive oral behaviors in preweaned calves through the weaning transition. Calves were randomly assigned to 1 of 3 treatments that differed by milk-feeding method (teat or bucket) and ad libitum access to chopped timothy hay: control, milk provided by bucket and no access to hay (CON; n = 10); milk provided by bucket and access to hay (H; n = 10); milk provided via a teat and access to hay (TH; n = 10). Calves had ad libitum access to concentrate and water, and were fed 6 L/d of pasteurized waste milk, divided into 2 meals. All calves were weaned by removing the second milk meal for 9 ± 2 d, beginning at 36 d of age. Daily concentrate and hay intake were recorded, and calves were weighed weekly to measure growth. We recorded the behavior of all calves using 2 s time-lapse video during time periods that encompassed milk meals, from 6000 h to 1000 h and 1600 h to 2000 h, on 2 consecutive focal days in wk 2 and 4. We continuously monitored lying time and activity using electronic data loggers. During the preweaning period, hay selection by H and TH calves was subject to a treatment × week interaction, with TH calves increasing hay intake to a greater extent over time. Similarly, we observed a tendency for a treatment × week interaction for hay dry matter intake. Before weaning, concentrate intake was subject to a treatment × week interaction, increasing to a greater extent over time for H and TH calves, but was greater overall for CON calves. As predicted, milk-feeding method and hay provision influenced the proportion of time devoted to feeding and non-nutritive behaviors. The CON calves spent the greatest amount of time performing non-nutritive sucking directed at the pen, TH calves the least, and H calves intermediate amounts. Considering the time TH calves sucked on their teat when milk was not present in addition to the time they spent sucking on pen fixtures, the total amount of time spent performing sucking behavior was similar between treatments. Although intake was similar across the weaning transition, CON calves had greater average daily gain than H calves, and TH calves were intermediate. Providing access to hay and milk via a teat during the milk-feeding stage decreased non-nutritive oral behaviors and influenced feeding behavior.